А) (2х+1)(х-1)= б)(3 - у²)(у-4)= в) а²+ (2-а)(а+5)= г) (b-1)(b²+b-2)= а) xy +3y+ха+3а =...

0 голосов
50 просмотров

А) (2х+1)(х-1)= б)(3 - у²)(у-4)= в) а²+ (2-а)(а+5)= г) (b-1)(b²+b-2)= а) xy +3y+ха+3а = б) 2а - ав + 6 - 3в а) 3х(1-2х)(2х+1)= 3х - 12х³ а) х³ - 4х² - х-4 = б) а³ - 3ав - 2а²в - 6б² =


Алгебра (146 баллов) | 50 просмотров
Дан 1 ответ
0 голосов

1) \: (2x + 1)( x - 1) = 2 {x}^{2} - 2x + x - 1 = 2 {x}^{2} - x - 1
2) \: (3 - {y}^{2} )(y - 4) = 3y - 12 - {y}^{3} + 4 {y}^{2} = - {y}^{3} + 4 {y}^{2} + 3y - 12
3) \: {a}^{2} + (2 - a)(a + 5) = {a}^{2} + 2a + 10 - {a}^{2} - 5a = 10 - 3a
4) \: (b - 1)( {b}^{2} + b - 2) = {b}^{ 3} + {b}^{2} - 2b - {b}^{2} - b + 2b = {b}^{3} - b

1) \: xy + 3y + xa + 3a = y(x + 3) + a(x + 3) = (y + a)(x + 3)
2) \: 2a - ab + 6 - 3b = a(2 - b) + 3(2 - b) = (a + 3)(2 - b)

1) \: 3x(1 - 2x)(2x + 1) = 3x - 12 {x}^{3} \\ 3x(1 - 4 {x}^{2} ) = 3x - 12 {x}^{3} \\ 3x - 12 {x}^{3} = 3x - 12 {x}^{3}

Далее не решается так как общие множители разные.
1) \: {x}^{3} - 4 {x}^{2} - x - 4 = {x}^{2} (x - 4) -( x + 4)
Далее не решается так как общие множители разные.й
2) \: {a}^{3} - 3ab - 2 {a}^{2} b - 6 {b}^{2} = {a}^{2} (a - 3b) - 2b( {a}^{2} - 3b)
Далее не решается так как общие множители разные.
(2.9k баллов)